Effects of Auditory Cues on Consumers' Affective States, Psychophysiological Responses, and Sensory Perception of Food - Kantono, Johanes Kevin (Auckland University of Technology, 2018)
The influence of auditory cues such as music or sounds has been largely remained unexplored in the area of food and sensory perception. This thesis investigates the influence of music and environmental sounds on temporal pleasantness and flavour perception. The influence of emotions on crossmodal interactions between auditory cues and food was further explored using subjective (e.g., valence, arousal, and dominance, and measures of specific emotional response), and objective (autonomic nervous system response, ANS) measures. Experiment One demonstrated that different environmental sounds influenced valence, arousal, and dominance ratings, which directly modulated the pleasantness of chocolate gelati. Chocolate gelati was rated as being highly valent (i.e., pleasant), and low in arousal and dominance when a café soundtrack was played. Listening to a café soundtrack also increased the pleasantness ratings of chocolate gelati. In Experiment Two, the effect of music varying in liking on temporal taste perception was explored using temporal dominance of sensations. Liked music was found to evoke positive emotions (e.g. satisfaction, happiness, and amusement), which was correlated with increased sweetness dominance and lowered bitterness dominance. On the contrary, listening to disliked music evoked negative emotions (e.g. contempt, disappointment, and disgust), which was correlated with increased bitterness dominance, and lowered sweetness dominance. Results also provided evidence that emotions evoked by music influenced taste perception. Experiment Three expanded Experiment Two by investigating the influence of music on gelati flavour in three different environments (laboratory, immersive, and commercial) using the ‘temporal check all that apply’ approach. In the laboratory environment, listening to liked music showed a higher citation rate of sweetness and milkiness, and listening to disliked music showed higher citation rates of bitterness and creaminess. Interestingly, modulation of taste perception (sweetness and bitterness) by music differed across the commercial venue and the laboratory environment. The immersive environment showed similar changes in temporal sensory perception to those obtained in the commercial environment. The effects of different environments on temporal flavour perception provided ecological validity to the research carried out in this thesis. Finally, Experiment Four demonstrated the changes in autonomic responses (i.e. cardiovascular, respiratory, and electrodermal response), subjective ratings of emotions, and temporal flavour perception, while listening to music varying in valence. A Partial Least Square Regression model showed that sweetness and creaminess were correlated with increased skin conductance and blood volume pulse amplitude, and decreased heart rate. On the other hand, bitterness, milkiness, and cocoaness were correlated with decreases in skin conductance and blood volume pulse amplitude, and increased heart rate. Further Partial Least Square Regression Path Modelling analysis confirmed that increased skin conductance and blood volume pulse amplitude were positively associated with negative emotions (i.e. anger, contempt, disappointment, and disgust), and negatively associated with positive emotions (i.e. amusement, enjoyment, love, happiness, and satisfaction). In contrast, heart rate was positively associated with positive emotions, and negatively correlated with negative emotions. This research provided quality empirical data in the impoverished field of crossmodal sensory science. Music influenced affective state, emotions, and autonomic nervous system responses that in turn influenced temporal flavour perception. Further research arising from study’s findings include confirming the influence of VAD on food pleasantness using more diverse food samples. In addition, individual differences should also be measured in order to explain and predict the within-panel inconsistencies manifest in sensory and emotional ratings of food. Future research could employ brain imaging technology to identify areas in the brain activated by sounds and how these areas relate to those invested in the sensory perception of food. This will provide further elucidation of the underlying mechanism governing the relationships between sound, taste, and flavour perception.
Keywords: Food; Crossmodal; Emotion; Sensory; Music; Electrophysiology